The Failure of State Oversight of Umrah Pilgrimage Organizers: An Analysis of Ministerial Accountability and Reformulation of the Regulatory Oversight Model - Adam Hidayat; Z. Zainuddin; Abdul Qahar (Manunggal Halim Jaya, 2026)
This study aims to analyze the failure of state oversight of Umrah pilgrimage organizers, emphasizing the accountability of the Ministry of Religious Affairs and the need for a more effective and equitable reformulation of the regulatory oversight model. The study focuses on how the existing supervisory structure has failed to prevent violations, and how these weaknesses impact the protection of pilgrims as users of religious services. This study uses a normative legal method with a statutory and conceptual approach. The legal materials used include primary, secondary, and tertiary legal materials, analyzed descriptively and prescriptively to identify legal problems and formulate normative solutions. The results indicate that the existing supervisory system is still administrative and formalistic, thus unable to reach the substantive aspects of Umrah implementation. This failure of supervision is characterized by a weak preventive function, delays in detecting violations, and suboptimal law enforcement. Furthermore, the ministry's accountability has not been optimal, as reflected in a lack of transparency, responsiveness, and limited public participation in the supervisory process. This condition indicates an imbalance between state authority and the effectiveness of its implementation. The findings of this study emphasize the need for a reformulation of the risk- and accountability-based oversight model, which integrates transparency, public participation, and the use of technology into the oversight system. This would ensure that oversight is not merely reactive but also capable of preventive and adaptive functions. This reform is expected to create a more effective oversight system, enhance ministry accountability, and provide optimal protection for the public.